Electromyographical analysis of double pole ergometry: standing vs. sitting - Tervo, J.; Watts, P.; Jensen, R. (ISBS - Conference Proceedings Archive (Konstanz), 2010)
This study assessed the difference in stand-up athlete's muscle activity of the rectus femoris in standing and sitting using a double pole ergometer. Five subjects participated in two technique specific peak VO2 tests, and a percentage of the maximum scores were used to determine stages for analysis of the electromyography data that was collected.